Soft Skills from Islamic Perspective for Maximal Students’ Learning Achievement - Aries Musnandar (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2020)
This study constitutes of conceptual and/or theoretical framework in Islamic values on soft skills as the main discussion. The purpose of instructional management is to handle teaching and learning process for better learning achievement results. Some researches have shown that soft skills can improve the students learning achievement. It is an urgent for any nation to have competent human capital investment in a Country. This article elucidates soft skills from Western adn Islam soft skills which can enhance the quality of students’ soft skills. The method of qualitative research is utilized in this study with case study approach. The research found that hard skills only contribute less than 20% of individual success. Meanwhile, 80% of success performance is contributed by soft skills. This research indicates soft skills as pivotal aspect for individual star performer not only in workplace but also in education sector. Therefore, soft skills will enable and improve also students’ potentials to reach the best learning achievement. At end, the author elaborates Islamic concept of soft skills. It is substantively that the Islamic teachings are comprehensive concepts to build and shape the noble behaviour of Muslims. At some extent, soft skills in Islamic view could be part of akhlak-adab or good personality which may benefit to other creatures. Finally, Islamic soft skills is inspired by the Quran and Sunnah